2019
DOI: 10.1504/ijbg.2019.099296
|View full text |Cite
|
Sign up to set email alerts
|

Management innovation and organisational performance: the mediating role of high performance organisation framework

Abstract: This study investigates the relationship between Management Innovation and Organisational Performance with the High Performance Organisation (HPO) factors of Continuous Improvement and Renewal, Workforce Quality and Long-term Orientation as mediators. From a survey among 186 managers of the insurance industry in Ghana and with the use of PLS-SEM, the results show that Management Innovation appears to have a direct influence on Organisational Performance but when Management Innovation is combined with the HPO f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…In previous research and papers on HPO, which we have published in the past years, we have already used the HPO definition as developed and proposed in this article. Other researchers have come across our proposed HPO definition and it seems to have struck a chord with them, possibly because they were also looking for an adequate definition, as an increasing number of them are using the proposed HPO definition and measurements in their own research (Abdullah et al , 2018; Do and Mai, 2020; Geleta, 2019; Hijal-Moghrabi et al , 2017; Honyenuga and Tuninga, 2013; Honyenuga et al , 2019; Kalimullah et al , 2019; Roijen et al , 2017; Thoman and Lloyd, 2018; Zbierowski, 2020).…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
“…In previous research and papers on HPO, which we have published in the past years, we have already used the HPO definition as developed and proposed in this article. Other researchers have come across our proposed HPO definition and it seems to have struck a chord with them, possibly because they were also looking for an adequate definition, as an increasing number of them are using the proposed HPO definition and measurements in their own research (Abdullah et al , 2018; Do and Mai, 2020; Geleta, 2019; Hijal-Moghrabi et al , 2017; Honyenuga and Tuninga, 2013; Honyenuga et al , 2019; Kalimullah et al , 2019; Roijen et al , 2017; Thoman and Lloyd, 2018; Zbierowski, 2020).…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
“…High-performance organizations lead the way and do not perform better because of only technical or human resources reasons [67][68][69]. Their success is based on a set of factors which should operate together to achieve the effect of synergy [70,71].…”
Section: Bailetti (2012)mentioning
confidence: 99%
“…Their finding suggests that the studied company improved their firm performance by utilizing the HPO framework. Honyenuga et al (2019) surveyed 186 managers from insurance companies in Ghana and found that the HPO framework mediates the direct impact of management innovation on organizational performance.…”
Section: Current Trends In Hpo Researchmentioning
confidence: 99%